Web architecture affects the functional response of the space web-builder Kochiura aulica against Trioza erytreae in the laboratory - Félix-Oliveira, Diogo (2022)
The “citrus greening disease” or huanglongbing (HLB) is caused by the Gram-negative bacteria Candidatus Liberibacter spp. One vector of HLB, the African citrus psyllid Trioza erytreae (del Guercio, 1918), was recorded for the first time in 2014, in mainland Spain, and since then, it has spread throughout the Iberian Peninsula. Spiders could be natural enemies of T. erytreae. In this work, we assessed the potential of a model spider species, selected according to the most abundant guild in the field, as a natural enemy of T. erytreae. Theridiidae was the most successful family, capturing adults of T. erytreae in the field. Kochiura aulica (Theridiidae) was selected as a model for functional response assays in the laboratory. The effect of web-building plasticity on the functional response of K. aulica was investigated using two types of arena. The spiders developed tubular-like or branch-like webs according to the spatial constraints. The web architecture significantly shifted the trapping efficiency of K. aulica. Functional responses for tubular and branch webs were both Type-II, but more psyllid prey were captured and killed in the tubular webs than in branch webs. In addition, significantly more psyllids survived in branch-like webs. Our results suggest that web architecture is a key factor driving the number of captured adults of the psyllid. Space web builders could be successful natural enemies of T. erytreae, although further research is needed to clarify the influence of web-building plasticity on the functional response and trapping efficiency of spiders.